Deforestation and the Development Dilemma: Challenges of Forest Governance in Indonesia - Sesario, Revi; Faradina, Anggia (Journal of Horizon, 2025)
This study aims to explore the complex relationship between deforestation, national development policies, and forest governance challenges in Indonesia. Using a qualitative-descriptive approach through literature review and policy analysis, the research reveals that Indonesia’s development model largely driven by extractive industries such as palm oil, mining, and logging has significantly contributed to the ongoing loss of tropical forest cover. The findings indicate that poor institutional coordination, overlapping regulations, tenure conflicts, and limited community participation are key barriers to achieving sustainable and equitable forest management. Moreover, while programs such as social forestry and customary forest recognition have shown potential in reducing deforestation, their effectiveness depends heavily on legal clarity, local institutional capacity, and consistent support from government stakeholders. This study emphasizes the urgent need for structural reform in forest policy, enhancement of local governance capacity, and multi-stakeholder collaboration to balance economic development with environmental conservation and social justice.